Performance Evaluation of Different SAR-Based Techniques on the 2019 Ridgecrest Sequence - Marco Polcari; Mimmo Palano; Marco Moro (Remote Sensing, 2021)
We evaluated the performances of different SAR-based techniques by analyzing the surface coseismic displacement related to the 2019 Ridgecrest seismic sequence (an Mw 6.4 foreshock on July 4th and an Mw 7.1 mainshock on July 6th) in the tectonic framework of the eastern California shear zone (Southern California, USA). To this end, we compared and validated the retrieved SAR-based coseismic displacement with the one estimated by a dense GNSS network, extensively covering the study area. All the SAR-based techniques constrained the surface fault rupture well; however, in comparison with the GNSS-based coseismic displacement, some significant differences were observed. InSAR data showed better performance than MAI and POT data by factors of about two and three, respectively, therefore confirming that InSAR is the most consolidated technique to map surface coseismic displacements. However, MAI and POT data made it possible to better constrain the azimuth displacement and to retrieve the surface rupture trace. Therefore, for cases of strike-slip earthquakes, all the techniques should be exploited to achieve a full synoptic view of the coseismic displacement field.